Assessment of thyroid and prolactin levels among the women with abnormal uterine bleeding - John, Jovita Deepthy; Damodaran, Vimala; Radhakrishnan, Shankar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Thyroid disorders are 10 times more common in women than men.1 Menstrual disturbances usually accompany clinical alterations in thyroid function and every clinician would have encountered altered menstrual pattern among women suffering from either hypo or hyper thyroidism. A high serum prolactin level can distrurb the follicular maturation and corpus luteum function, and leads to inhibition of normal pulsatile secretion of gonadotrophin-releasing hormone in hypothalamus resulting in anovulation. The aim of the study was to assess the thyroid and the prolactin levels among the women with abnormal uterine bleeding and to evaluate the association between them by comparing with normal females. Methods: A cross sectional study was conducted for a period of one year between Jan 2016 and December 2016 in our institution at the gynaecology OPD. Patients in the age group of 15 to 45 with the complaints of abnormal uterine bleeding and with the ultrasound findings showing normal uterus and ovary were included in the study. Hundred age and sex matched controls without any complaints of abnormal uterine bleeding in the age group of 15 – 45 years were also included in the study. Free T3, Free T4, TSH and prolactin estimation was done by chemiluminescent immunoassay for both the patients and the controls. Results: The mean TSH levels among the cases were much higher than that of the controls and the difference in the levels found to be statistically significant. Similarly, hyperprolactinemia was found in 18 cases when compared to 2 cases in controls and the mean prolactin levels were higher in cases. The serum prolactin levels and the serum TSH levels showed a perfect positive correlation which indicates that as the TSH level increases prolactin levels also increases with the R value >0.5. Conclusions: Early detection of hypothyroidism in such subjects saves the patient from recurrent curettage and at times hysterectomy. The ﬁnancial implications of screening for prolactin/thyroid hormone abnormalities will have to be evaluated before a general recommendation can be made.